PERSEPSI PUSTAKAWAN TERHADAP GAYA KEPEMIMPINAN TRANSFORMASIONAL PIMPINAN (STUDI KASUS UPT. PERPUSTAKAAN UNIVERSITAS SYIAH KUALA) - Badratun Nafis (Perpustakaan Nasional RI, 2020)
Preliminary. This study aims to determine and measure the librarians' perceptions of the leadership style of the transformational leadership through four aspects of its characteristics, consisting of; (1) Idealized Influence; (2) Inspirational Motivation; (3) Intellectual Stimulation; and (4) Individual Consideration at Syiah Kuala University Library. Research methods. This research is quantitative descriptive, because the data obtained are in the form of descriptive statistics and percentages. The method used in this research is survey. Data collection techniques using instruments by distributing questionnaires made using a Likert scale, so that researchers can measure perceptions in this study. The instrument numbered 27 questionnaires with 20 questions, consisting of four aspects of the transformational leadership style. Results and Discussion. The results of the questionnaire from the four aspects obtained were; (1) The idealized influence is categorized as very good, with a percentage of 90.37%. This aspect is the aspect that gets the highest score from other aspects; (2) Inspirational motivation is also categorized as very good, with a percentage of 87.11%; (3) Intellectual stimulation obtained results in the good category, with a percentage of 84.30% .; (4) Individual Consideration gets the lowest score from the three other aspects, but it is still in good category, with a percentage of 82.37%.Conclusion. Librarians' perceptions of the transformational leadership style of the leaders of Syiah Kuala University Library from the four aspects obtained a total score of 2,323 from a maximum score of 2,700 with a percentage of 86.04% (very good).